On-Table Zenith® CE Fenestrated Stent Graft Modifcation for the Treatment of Delayed Type Ia Endoleak - Pais, F (2022)
INTRODUCTION: Delayed type Ia endoleaks are often associated with proximal extension of the aneurysmal degeneration to the juxtarenal aortic segment. Endovascular treatment of type Ia endoleaks secondary to aortic neck dilatation can raise many technical challenges related to the previous implanted stent graft. CASE REPORT: The authors present a clinical case of an 84 year-old man, with a past medical history of atrial fbrillation, acute ischemic stroke, hypertension and dyslipidemia, that initially underwent an EVAR for a 5.5.cm infrarenal AAA with a TREO Bolton® endograft. After 3 years of follow-up, the CTA scan showed a delayed type Ia endoleak secondary to aortic neck dilatation with signifcant growth of the aneurysmatic sac. An endovascular proximal extension was planned, using a Zenith Fenestrated (ZFEN) platform (Cook Medical, Bloomington, Ind) but the short distance to the previous EVAR bifurcation did not allow the implantation of a standard 94cm CE fenestrated stent graft. To overcome this challenge, on-table modifcation of the fenestrated stent graft was performed by cutting the distal aortic stent. The stent graft was partially deployed on-table, the distal stent was cut with thermocautery, and the device was re-sheathed. The fenestrated cuff was then implanted in the standard fashion with target vessel catheterization and stenting. Two aortic covered stents (Aortic Begraft Bentley® 18mm) were implanted inside each iliac limb of the previous EVAR and sealed proximally in a parallel graft confguration on the fenestrated cuff. The fnal completion angiogram demonstrated perfusion of the visceral arteries, resolution of the Ia endoleak and without further endoleaks, as well as perfusion of both hypogastric arteries. At two months of follow up, the patient remains asymptomatic and the CTA scan showed resolution of the type Ia endoleak but the presence of a late type II endoleak. DISCUSSION: Delayed type Ia endoleaks associated with proximal extension of the aneurysmal degeneration to the juxtarenal aortic segment, can raise some technical diffculties related to the previous implanted stent graft. Careful evaluation of patient anatomy and previous endografts should be done in planning for these procedures. On table physician modifcation of stent grafts is a valid solution to overcome challenging cases limitations. Further long-term follow-up is needed.